2014
DOI: 10.1002/cbf.3042
|View full text |Cite
|
Sign up to set email alerts
|

Selective TRAIL‐induced cytotoxicity to lung cancer cells mediated by miRNA response elements

Abstract: Lung cancer is among the most common cancers, and the current therapeutic strategies are still inefficient in most cases. Tumour necrosis factor-related apoptosis-inducing ligand (TRAIL) is a promising biological agent for cancer treatment because of its potent pro-apoptotic effect on cancer cells. However, TRAIL also induces apoptosis in normal cells and therefore may cause toxicity to normal tissues if clinically applied. To address this issue, we inserted microRNA response elements (MREs) of miR-133a, miR-1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Prx1 induces TRAIL ( tumor necrosis factor–related apoptosis-inducing ligand ) resistance by suppressing the redox-dependent activation of caspase [90]. TRAIL is a biological agent that induces apoptosis of cancer cells and is considered a promising anticancer agent [91]. Down-regulation of Prx1 using RNA interference or chemical agents like dioscin results in the induction of apoptosis in tumor cells [92; 93].…”
Section: The Srx-prx Axis In Tumorigenesis and Cancer Progressionmentioning
confidence: 99%
“…Prx1 induces TRAIL ( tumor necrosis factor–related apoptosis-inducing ligand ) resistance by suppressing the redox-dependent activation of caspase [90]. TRAIL is a biological agent that induces apoptosis of cancer cells and is considered a promising anticancer agent [91]. Down-regulation of Prx1 using RNA interference or chemical agents like dioscin results in the induction of apoptosis in tumor cells [92; 93].…”
Section: The Srx-prx Axis In Tumorigenesis and Cancer Progressionmentioning
confidence: 99%
“…As the incidence of lung adenocarcinoma has rapidly increased, it has become a major pathological type of lung cancer. 4 Revealing the molecular pathogenesis of lung adenocarcinoma may enable improvement in the diagnosis and treatment of this disease.…”
Section: Introductionmentioning
confidence: 99%
“…Resistance occurs when certain genetic or epigenetic changes make the treatment ineffective against the tumor cells [ 174 , 175 ]. MiR-221 and miR-222 were first discovered to be involved in the development of some epithelial cancers [ 176 ]. Subsequently, these two miRNAs were found to be upregulated in NSCLC and further investigation revealed that they regulate the tumor suppressors PTEN and TIMP3 [ 177 ].…”
Section: Research Focused On Therapeutic Applicationsmentioning
confidence: 99%